Study on thermoacoustic instabilities in an aircraft engine combustor using 1D network model - Juchan Son; Seungchai Jung; Shaun Kim; Daesik Kim (Case Studies in Thermal Engineering)
The purpose of this study was to evaluate the combustion instability characteristics of target aircraft combustors under development using network thermoacoustic (TA) models. The eigenfrequencies of the aeroengine combustor and their mode shapes were calculated using the TA model, and the growth rates of the acoustic resonances were interpreted from a feedback analysis combined with the combustion process. Two different forms of the flame transfer function (FTF) were considered to reflect the flame responses to the incoming flow fluctuations in feedback coupling. To derive the time delay between the velocity fluctuations from the nozzle to the flame surface, a steady-state computational fluid dynamics (CFD) calculation was performed under actual combustor operating conditions. The acoustic analysis results using the current 1D network model showed that both the eigenfrequency and mode distribution of each resonance were reasonably predicted by comparing it with the 3D Helmholtz calculation results. From the feedback instability analysis, it was found that both the frequency and growth rates of the instabilities were significantly affected by the change in gain and time delay of the FTF.